Catalyst or Cause? Legislation and the Demise of Machine Politics in Britain and the United States. Issue 4 (November 2014) - Camp, Edwin; Dixit, Avinash; Stokes, Susan
<x xml:space="preserve">Abstract</x> In the nineteenth century, British and American parties competed by hiring electoral agents to bribe and treat voters. British parties abruptly abandoned this practice in the 1880s. The conventional explanation is that legislation put an end to agent‐mediated distribution. But this explanation leaves many questions unanswered. Why did the parties use agents for decades, even though they imposed great expense on candidates and were viewed as untrustworthy? And why, after decades of half‐hearted reforms, did the House of Commons pass effective antibribery reforms only in 1883? In our formal model, parties hire agents to solve information problems, but agent‐mediated distribution can be collectively suboptimal. Legislation can serve as a credibility device for shifting to less costly strategies.